The model of charnockite formation process in Thala hills, East Antarctica - Miasnikov, O.B. (Ukrainian Antarctic Journal, 2014)
The research was performed in 2008-2009 within Belarus Government target program with the 54-th Russian Antarctic expedition. Geological mapping was carried out along with geochemical survey of Precambrian basement of Thala hills in western Enderby Land, Antarctica (lat 67°38,7’S ÷ 67°41’S; long 46°02,7’E ÷ 46°14’E). Peculiarities of geophysical fields correspond to the different petrophysical conditions. In the outcrops within Thala hills, the field relations of plagiogneisses facies, migmatitic and plutonic rocks of charnockite and post-tectonic granitoid affinities are well exposed. Four types of main petrographic and petrophysical heterogeneities were singled out: 1) protolyth - relic two pyroxene amphibole, biotite plagiogneisses (pg); 2) intermediate hybrid amphibole-pyroxene-plagioclase-quartz-feldspathic charnockitic enderbites (čeg); 3) enclosing amphibole-feldspathic-quartz-plagioclase charnockites (čg); 4) in cores – ultrametamorphic feldspathic-quartz-plagioclase-amphibole-biotite streamy rapakivi-gneissic charnockites (hybrids) (čmg). The rocks correspond to the dominant processes of tectonic thermal activation of the four geochronological borders. The rocks architectonics reflects evolutionary succession of events, i.e. a change of direction of granitization processes from lateral (↔) crustal to vertical (↕) intrusive ones. The territory structure of Thala hills is represented as an ordered linear-dome model of Precambrian structural and compositional evolution: protolyth plagiogneiss ↔, intermediate charnockitic enderbite ↔, enclosing charnockite ↔, core - streamy rapakivioid charnockite.